The public institution for integrated maritime domain management in Croatia : role and functions - Vuković, Ante, pravnik (Array, 2020)
The aim of this article is the analysis of the existing maritime domain management system in Croatia, with a special attention to the port system management compared to maritime domain and port management systems in Italy, Spain and France. The research shows that Croatia does not have the strategy for integrated management of maritime domain. In respect of the size of national territory covered by maritime domain and its importance for the general Croatian economy, especially for tourism, we believe that is undeniable that this issue should be regulated as follows: the newly established Public Institution for Integrated Maritime Domain Management should manage the maritime domain and it should have branches on regional level. Thereby the management system of maritime domain would finally be consistent, managed from one place and under management of experts. At the same time, the strategy would be the base for the reform of the existing MDSA or for the completely new law on maritime domain and seaports.